Parrot populations and habitat use in and around two lowland Atlantic forest reserves, Brazil - Marsden, S. J.; Whiffin, M.; Sadgrove, L.; Guimaraes, P. (Elsevier B.V., 2000)
We estimated population sizes of parrots in a large (Sooretama/Linhares) and a small (Porto Seguro) lowland Atlantic forest reserve, and examined their habitat associations within the reserves, and their use of forest fragments. In Sooretama, most species had estimated populations between 1000 and 20,000 individuals, but in the smaller reserve population densities were low and all but one species had population estimates < 500. Two Amazons, including the 'Endangered' Amazona rhodocorytha, were strongly linked to primary forests whereas the 'Vulnerable' Pyrrhura cruentata was associated with non-pristine forest. There was considerable movement of parrots between the Sooretama reserve and the surrounding country with Amazona species tending to fly into the reserve during the mornings, and the macaw Propyrrhura maracana flying out. Other species, notably P. cruentata and P. leucotis, were never recorded away from the reserve. Most parrot populations in the region are likely to be small, and the substantial populations around Sooretama make this reserve a parrot stronghold. It is crucial that fire, illegal logging and parrot capture are adequately controlled within Sooretama, and there is a strong argument for extending conservation management efforts to areas immediately outside the reserve. (C) 2000 Elsevier B.V. Ltd. All rights reserved.
Keywords: parrots; Atlantic forest; population sizes; Amazona; Pyrrhura